Combination therapy of Epidermal Growth Factor and Growth Hormone-Releasing Hexapeptide in acute ischemic stroke: a phase I/II non-blinded, randomized clinical trial - Hernández-Bernal, Francisco; Estenoz-García, Donner; Gutiérrez-Ronquillo, Juan H.; Martín-Bauta, Yenima; Catasús-Álvarez, Karen; Gutiérrez-Castillo, Mario; Guevara-Rodríguez, Marbelys; Castro-Jeréz, Aliuska; Fuentes-González, Yoandra; Pinto-Cruz, Yulemis; Valenzuela-Silva, Carmen; Muzio-González, Verena L.; et al. (Frontiers in Neurology, 2024)
Objective: This study tested the hypothesis that a neuroprotective combined therapy based on epidermal growth factor (EGF) and growth hormone releasing hexapeptide (GHRP6) could be safe for acute ischemic stroke patients, admitting up to 30% of serious adverse events (SAE) with proven causality.Methods: A multi-centric, randomized, open-label, controlled, phase I-II clinical trial with parallel groups was conducted (July 2017 -January 2018). Patients aged 18-80 years with a computed tomography-confirmed ischemic stroke and less than 12 hours from the onset of symptoms, were randomly assigned to the study groups I (75µg rEGF + 3.5 mg GHRP6 i.v., n=10), II (75 µg rEGF + 5 mg GHRP6 i.v., n=10), or III (standard care control, n=16)). Combined therapy was given BID for 7 days. The primary endpoint was safety over 6 months. Secondary endpoints included neurological (NIHSS) and functional (Barthel index and modified Rankin scale (mRS)) outcomes.The study population had a mean age of 66 ± 11 years, 21 were men (58.3%), a baseline median NIHSS score of 9 (95% IC: 8;11) and mean time to treatment of 7.3 ± 2.8 h. Analysis were by intention to treat. SAEs were reported in 9/16 (56.2%) patients in control group, 3/10 (30%) patients in Group I (Odds Ratio (OR): 0.33; 95% CI: 0.06 to 1.78), and 2/10 (20%) patients in Group II (OR: 0.19; 95% CI: 0.03 to 1.22); only two events in one patient of Group I were attributed to the intervention treatment. Compliance with the study hypothesis was greater than 0.90 in each group. Patients treated with EGF+GHRP6 had a favorable neurological and functional evolution at both 90 and 180 days, evidenced by inferential analysis of NIHSS, Barthel and mRS and by their moderate to strong effect size. At six months, proportion analysis evidenced a higher survival of patients treated with the combined therapy. Ancillary analysis including merged treated groups and utility-weighted mRS also showed a benefit of this combined therapy.Conclusions: EGF + GHRP6 therapy was safe. The functional benefits of treatment in this study supported a Phase III study.